2006
DOI: 10.1149/1.2356334
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Hysteresis Behavior of Low Temperature Polycrystalline Silicon Thin Film Transistors

Abstract: Image sticking of AMOLED is caused by the property variation of driving transistors. In this paper, we investigated the hysteresis behavior of p-type p-Si thin film transistors as driving device for AMOLED. As the temperature increase, it was observed that hysteresis phenomenon was suppressed. This can be explained by that the trapping and de-trapping rate of carriers is much faster in high temperature than in room temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…[12] Hysteresis phenomenon was suppressed with increase of the panel temperature up to 100 o C due to the faster trapping/detrapping rate in high temperature. [13] The hysteresis was reported to be 0.20V at 100 o C. Although there have been many trials to reduce the hysteresis by surface plasma treatment, annealing, thin active, and heating the panel, the minimum hysteresis was reported to be around 0.17V for 50nm-thick poly-Si channel TFTs. In this reports, we showed that LTPS TFT's hysteresis could be reduced below 0.1V by applying the combinational adjustment of defect reduction in poly-Si and surface potential (φs) increase in channel.…”
Section: Introductionmentioning
confidence: 99%
“…[12] Hysteresis phenomenon was suppressed with increase of the panel temperature up to 100 o C due to the faster trapping/detrapping rate in high temperature. [13] The hysteresis was reported to be 0.20V at 100 o C. Although there have been many trials to reduce the hysteresis by surface plasma treatment, annealing, thin active, and heating the panel, the minimum hysteresis was reported to be around 0.17V for 50nm-thick poly-Si channel TFTs. In this reports, we showed that LTPS TFT's hysteresis could be reduced below 0.1V by applying the combinational adjustment of defect reduction in poly-Si and surface potential (φs) increase in channel.…”
Section: Introductionmentioning
confidence: 99%